HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TERHADAP PERILAKU KUNJUNGAN PEMERIKSAAN KEHAMILAN (Studi pada Puskesmas Segala Mider Kelurahan Segala Mider Kecamatan Tanjung Karang Barat, Kota Bandar Lampung) - Ranti, Yunita Fitri; Ikram, Ikram (SOCIOLOGIE, 2013)
Maternal and child health problems is a national problem that needs to be given priority, especially for pregnant women. The gestation period is a dangerous time for babies / toddlers because there is a higher risk of infection during this process, and its best to do a pregnancy since the mother was pregnant. In addition, a good knowledge and attitudes that support is one of the factors related to behavior, to perform routine antenatal visits. The study aims to look at the relationship of knowledge and attitudes towards the behavior of pregnant women prenatal care visits. The hypothesis proposed is that the relationship between knowledge and attitude towards the behavior of pregnant women prenatal visit. This research is explanatory. Explanatory research intends to highlight the relationship between the study variables and test hypotheses that have been formulated previously. This study aims to investigate what happened and looking back on things that have been and to determine the factors that can lead to the onset of an event. analysis of the data used is quantitative data analysis. Quantitative data analysis is a type of data that can be measured directly or can be calculated more precisely. Subsequent to the processing of data, the analysis used is to use a cross tables. The statistical test used in this study is to look at the relationship between two independent and dependent variables using simple linear regression hypothesis and multiple linear regression. From the results of the study showed that the relationship There Maternal Knowledge and Attitudes Toward Pregnancy inspection visits.Keywords: Maternal knowledge, behavior, pregnant women, prenatalÂ